2019
DOI: 10.1002/em.22316
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity as a parameter in surface water monitoring programs—opportunity for water quality improvement

Abstract: Effect-based analyses are being recognized as excellent tools to a comprehensive and reliable water quality evaluation to complement physical and chemical parameters. The Salmonella/microsome mutagenicity test was introduced in the São Paulo State water quality-monitoring program in 1999 and waters from 104 sites used to the production of drinking water were analyzed. Samples were tested after organic extraction, using the microsuspension version of the Salmonella/microsome assay with strains TA98 and TA100 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The Salmonella preincubation assay is a modified Ames mutagenicity assay (Kargalioglu et al, 2002;Plewa et al, 2004b), which is run in conjunction with the Salmonella typhimurium microplate cytotoxicity assay and was applied to assess DBPs. Most of the studies on mutagenicity testing of water quality simply reported a positive or negative response (Berninger et al, 2019;Albergamo et al, 2020), without determining an effect concentration (EC) or bioanalytical equivalent concentration but there is also guidance on how to interpret such data (Roubicek et al, 2020). Table 10.33 includes only studies that have reported an EC value, with studies reporting the effect concentration inducing a revertant ratio of 1.5 (EC RR1.5 ).…”
Section: Referencementioning
confidence: 99%
“…The Salmonella preincubation assay is a modified Ames mutagenicity assay (Kargalioglu et al, 2002;Plewa et al, 2004b), which is run in conjunction with the Salmonella typhimurium microplate cytotoxicity assay and was applied to assess DBPs. Most of the studies on mutagenicity testing of water quality simply reported a positive or negative response (Berninger et al, 2019;Albergamo et al, 2020), without determining an effect concentration (EC) or bioanalytical equivalent concentration but there is also guidance on how to interpret such data (Roubicek et al, 2020). Table 10.33 includes only studies that have reported an EC value, with studies reporting the effect concentration inducing a revertant ratio of 1.5 (EC RR1.5 ).…”
Section: Referencementioning
confidence: 99%
“…It is noteworthy however that in the seminal paper the smallest change of mutant frequencies judged to be significant was a 4.4-fold increase [58]. In a study analyzing the mutagen-content of natural waters using a similar technique, the minimal effective dose required for doubling the mutant frequency (MED2) was declared as a relevant parameter to be calculated for all samples [59]. When reporting the mutagenicity of chemicals, many times the dose-dependent effect is demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy however that in the seminal paper, the smallest change of mutant frequencies judged to be significant was a 4.4-fold increase [59]. In a study analyzing the mutagen-content of natural waters using a similar technique, the minimal effective dose required for doubling the mutant frequency (MED2) was declared as a relevant parameter to be calculated for all samples [60]. When reporting the mutagenicity of chemicals, many times the dose-dependent effect is demonstrated.…”
Section: Plos Onementioning
confidence: 99%